2021
DOI: 10.21597/jist.843569
|View full text |Cite
|
Sign up to set email alerts
|

Iğdır İlinde Domates Üretim Maliyetinin Belirlenmesi

Abstract: Bu çalışmanın amacı Iğdır İlinde domates üretim maliyetini belirlemektir. Çalışmada Iğdır ve İlçelerinde Basit Tesadüfi Örnekleme Yöntemi ile belirlenen 105 adet domates üreten işletmeden elde edilen veriler kullanılmıştır. Domates maliyetinin hesaplanmasında "Tek Ürün Bütçe Analiz Yöntemi" kullanılmıştır. Çalışmada işletmelerin ortalama 6.07 da alanda domates ürettikleri ve dekara 5 454.76 kg ürün elde ettikleri belirlenmiştir. Ürün satış fiyatı 0.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
0
3
0
1
Order By: Relevance
“…In the bakery industry, mixed microbial cultures such as kefir can be used naturally to prevent microbial spoilage and staleness and to extend shelf life [31]. Kefir is known to repair and strengthen the immune system [32]. It can be thought that it supports the immune system, since it is possible that kefir can be used during the production of simit.…”
Section: Food Consumption Frequency Questionnairementioning
confidence: 99%
“…In the bakery industry, mixed microbial cultures such as kefir can be used naturally to prevent microbial spoilage and staleness and to extend shelf life [31]. Kefir is known to repair and strengthen the immune system [32]. It can be thought that it supports the immune system, since it is possible that kefir can be used during the production of simit.…”
Section: Food Consumption Frequency Questionnairementioning
confidence: 99%
“…Yine yaz döneminde gündüzleri koyunlar, çardak adı verilen ve taş yığma, üzeri çalı, çırpı ile kapatılmış (Şekil 4.2. ), bir insanın ancak emekleyerek girebileceği barınaklar bulunmaktadırlar (Türedi ve Savaş, 2015). Kış döneminde ise yarı açık, önünde gezinti alanı bulunan, yine taş yığma veya çalılardan örülü ağıllarda barındırılmaktadırlar.…”
Section: şEkil 41: çAnakkale Ilinde Yetiştiriciliği Yapılan Sakız Koy...unclassified
“…[48] reported the net profits of tomatoes as 1804 and 2513 $ ha -1 for different agricultural lands. [49] reported that the net income in tomato farming is 7710 $ ha -1 in Iğdır Province. [50] stated that tomato producers in Nigeria cultivate the tomatoes profitably but the farmers must constantly create different efficiency methods and future studies must be conducted about sustainable production.…”
Section: E Economic Analysismentioning
confidence: 99%